Rational design of coumarin derivatives as antituberculosis agents - Mali, Hemlata M.; Sabale, Sandip S.; Degani, Mariam S.; Borkute, Rachana; Choudhari, Amit S.; Sarkar, Dhiman; Krishna, Vagolu Siva; Sriram, Dharmarajan (Future Medicinal Chemistry, 2018)
A series of coumarin derivatives was designed as potential antituberculosis agents. Results: The compounds were screened against active and dormant Mycobacterium tuberculosis (Mtb). Compounds 3k and 3n were found to have the most promising activity against replicating MtbH37Rv exhibiting minimum inhibitory concentration of 4.63 and 9.75 mu M respectively. The compounds were also effective against dormant MtbH37Rv exhibiting more potency than the standard drugs, isoniazid and rifampicin. The compounds were found to be non-cytotoxic against human cell lines. Conclusion: This study provides promising antituberculosis agents that are effective against replicating as well as dormant Mtb and can thus act as potential leads for further development.

Synthesis and biological evaluation of 2,4,5-trisubstituted thiazoles as antituberculosis agents effective against drug-resistant tuberculosis - Karale, Uttam B.; Krishna, Vagolu Siva; Krishna, E. Vamshi; Choudhari, Amit S.; Shukla, Manjulika; Gaikwad, Vikas R.; Mahizhaveni, B.; Chopra, Sidharth; Misra, Sunil; Sarkar, Dhiman; Sriram, Dharmarajan; Dusthackeer, V. N. Azger; et al. (European Journal of Medicinal Chemistry, 2019)
The dormant and resistant form of Mycobacterium tuberculosis presents a challenge in developing new anti-tubercular drugs. Herein, we report the synthesis and evaluation of trisubstituted thiazoles as antituberculosis agents. The SAR study has identified a requirement of hydrophobic substituent at C2, ester functionality at C4, and various groups with hydrogen bond acceptor character at C5 of thiazole scaffold. This has led to the identification of 13h and 13p as lead compounds. These compounds inhibited the dormant Mycobacterium tuberculosis H37Ra strain and M. tuberculosis H37Rv selectively. Importantly, 13h and 13p were non-toxic to CHO cells. The 13p showed activity against multidrug-resistant tuberculosis isolates. (C) 2019 Elsevier Masson SAS. All rights reserved.